Links Between Conspiracy Thinking and Attitudes Toward Democracy and Religion: Survey Data From Poland - Czech, Franciszek (Politics and governance, 2022)
Religion and democracy are not only social institutions but also objects of attitudes. This article focuses on conspiracy thinking and its links with attitudes toward religion and democracy. Due to its contextual character, the study is limited to Poland and the article intends to report the data on the subject from surveys conducted in this country. In terms of conspiracy thinking and attitudes toward religion, the literature review of existing Polish survey data (Study 1) led to the conclusion that not all types of religious life are correlated with conspiracy thinking. Individual spirituality (the centrality of religiosity and the quest orientation of religiosity) matters less in terms of conspiracy thinking than religion understood as a specific element of ideology (Polish Catholic nationalism, religious fundamentalism, or collective narcissism). In terms of attitudes toward democracy (Study 2), the original dataset is coded in a new way (as categorial variables) and then presented. It suggests that, contrary to earlier research, conspiracy thinking does not necessarily lead to the support of anti-democratic attitudes. Alienation as much as radicalization might be a consequence of conspiracy thinking. There is no significant difference in terms of conspiracy thinking between adherents of authoritarian rules and conditional democrats, indifferent democrats, or people with ambivalent opinions on democracy, described in comparative research on political culture as dissatisfied democrats or critical citizens. The lower level of conspiracy thinking has been identified only among consistent democrats.